2014
DOI: 10.1111/jcmm.12206
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 regulates MAPK pathways in vitiligo skin: insight into the molecular pathways of cell survival

Abstract: Vitiligo is an acquired and progressive hypomelanotic disease that manifests as circumscribed depigmented patches on the skin. The aetiology of vitiligo remains unclear, but recent experimental data underline the interactions between melanocytes and other typical skin cells, particularly keratinocytes. Our previous results indicate that keratinocytes from perilesional skin show the features of damaged cells. Sirtuins (silent mating type information regulation 2 homolog) 1, well-known modulators of lifespan in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 81 publications
5
55
0
Order By: Relevance
“…SIRT1 activity was assessed using SIRT1 Direct Fluorescent Screening Assay Kit (Cayman, Ann Arbor, MI, USA) as previously described [4]. Compared with fibroblasts from healthy subjects, psoriatic cells exhibit a marked decrease (325.8 ± 58.42 vs 724.3 ± 123.9, p \ 0.0001) in SIRT1 activity.…”
mentioning
confidence: 99%
“…SIRT1 activity was assessed using SIRT1 Direct Fluorescent Screening Assay Kit (Cayman, Ann Arbor, MI, USA) as previously described [4]. Compared with fibroblasts from healthy subjects, psoriatic cells exhibit a marked decrease (325.8 ± 58.42 vs 724.3 ± 123.9, p \ 0.0001) in SIRT1 activity.…”
mentioning
confidence: 99%
“…Increased expression of miR-9 downregulates SIRT1 resulting in melanocytes apoptosis in vitiligo (Saunders et al 2010). SIRT1 has been shown to regulate stress-activated MAPK pathway via Akt and ASK1 in vitiligo keratinocytes (Becatti et al 2014). Previous studies have demonstrated the influence of miR-145 on the genes involved in the pigmentation process (Dynoodt et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial membrane potential was assessed as previously reported [24] using tetramethylrhodamine methyl ester perchlorate (TMRM), a lipophilic potentiometric fluorescent dye that distributes between the mitochondria and cytosol in proportion to Δψ by virtue of its positive charge. At low concentrations, the fluorescence intensity depends on dye accumulation in mitochondria, which in turn is directly related to mitochondrial potential.…”
Section: Mitochondrial Membrane Potential (δψ)mentioning
confidence: 99%